The use of Kutikulin for treatment and prevention of gastrointestinal diseases in calves and piglets - M. V. Koryukina; V. N. Makarova; O. B. Badeeva; I. N. Simanova (Ветеринария сегодня)
The global economy dictates more and more stringent  requirements  for the quality and volumes of products consumed. Veterinary professionals have to look for medicinal products that have a sparing effect on the animal body and, at the same time, are capable of eliminating  disease causes. The paper presents  the results of tests of Kutikulin, a product made at the Vologda Branch of the FSC VIEV, which consists of chicken gizzard cuticle containing a keratoid secretion and a number of biologically active enzymes. It is a non-toxic, water-insoluble, odourless yellow-green powder with a bitterish taste. When Kutikulin was used to treat newborn calves with a mild dyspepsia resulting from various alimentary causes, the disease duration averaged 2.9 days, recovery rates in the groups were approximately the same (96.6–96.9%). Kutikulin treatment of older calves allowed to reduce the duration of treatment by almost a day, to increase recovery rates by 4.8% and to decrease the number of deaths by 1.6 times.When used for preventive purposes in weaned piglets, Kutikulin helped to decrease morbidity in groups 1, 3 and 5 (test groups) by 2.7, 8.9 and 1.8 times, respectively, as compared with control groups. Its preventive effectiveness was found to be the highest in group 3 (test) piglets that received Kutikulin on a group basis with a liquid feed at a dose of 1.0 g once a day during 3 consecutive days. Along with a shorter disease duration, test group animals also demonstrated  less pronounced clinical symptoms. Thus, the use of Kutikulin reduces gastrointestinal disease morbidity and mortality in calves and piglets.